Characterization of mortar with pennisetum purpureum ashes as cement replacement material - W. I., Mohd Haziman; Mohammed Yahya, Al-Fasih; Nik Nadia Amira, Nik Pa; Putra Jaya, Ramadhansyah; Setiawan, Muhammad Ikhsan (IIUM, 2021)
In this study, the properties of mortar such as standard consistency, setting time, compressive strength, and water absorption rate were investigated. The cement was replaced with Pennisetum purpureum ashes (PPA) in different particle sizes and dosages. PPA was produced in greyish-white ash with total reactive oxides ranging from 37% to 41.1%. Pennisetum purpureum grass (PPG) was burned with a controlled process at 350 °C for the first 3 hours and 600 °C for another 3 hours at a heating rate of 10 °C/min. Then, PPG was ground in three different grinding durations (1, 3, and 6 hours) producing ashes with particle sizes of 10.58 µm, 10.25 µm, and 9.30 µm, respectively. The physical, chemical, and microstructural properties of PPA were evaluated through several tests; particle size analysis, X-ray diffraction analysis, loss on ignition, and chemical composition. Results indicated that PPA is more suitable for use as filling material as a substitute for cement than pozzolanic material as its reactive oxides are less than 50%. The 15% 6H-PPA at 28 days was found to be the optimum PPA replacement dosage and grinding time with cement as it achieved the highest strength and lower water absorption rate among all samples at 7 and 28 days.